Crystallization and X-ray structure analysis of a thermostable penicillin G acylase from alcaligenes faecalis - Varshney, Nishant Kumar; Kumar, R. Suresh; Ignatova, Zoya; Prabhune, Asmita; Pundle, Archana; Dodson, Eleanor J.; Suresh, C. G. (Acta Crystallographica Section F-Structural Biology and Crystallization Communications, 2012)
{The enzyme penicillin G acylase (EC 3.5.1.11) catalyzes amide-bond cleavage in benzylpenicillin (penicillin G) to yield 6-aminopenicillanic acid, an intermediate chemical used in the production of semisynthetic penicillins. A thermostable penicillin G acylase from Alcaligenes faecalis (AfPGA) has been crystallized using the hanging-drop vapour-diffusion method in two different space groups: C2221, with unit-cell parameters a = 72.9
Keywords: calcium binding; disulfide bridges; Ntn hydrolases; orthorhombic form; tetragonal form; Thermostability

Cloning, overexpression, crystallization and preliminary X-ray crystallographic analysis of a slow-processing mutant of penicillin G acylase from Kluyvera citrophila - Varshney, Nishant Kumar; Ramasamy, Sureshkumar; Brannigan, James A.; Wilkinson, Anthony J.; Suresh, C. G. (Acta Crystallographica Section F-Structural Biology and Crystallization Communications, 2013)
{Kluyvera citrophila penicillin G acylase (KcPGA) has recently attracted increased attention relative to the well studied and commonly used Escherichia coli PGA (EcPGA) because KcPGA is more resilient to harsh conditions and is easier to immobilize for the industrial hydrolysis of natural penicillins to generate the 6-aminopenicillin (6-APA) nucleus, which is the starting material for semi-synthetic antibiotic production. Like other penicillin acylases, KcPGA is synthesized as a single-chain inactive pro-PGA, which upon autocatalytic processing becomes an active heterodimer of alpha and beta chains. Here, the cloning of the pac gene encoding KcPGA and the preparation of a slow-processing mutant precursor are reported. The purification, crystallization and preliminary X-ray analysis of crystals of this precursor protein are described. The protein crystallized in two different space groups, P1, with unit-cell parameters a = 54.0